2019
DOI: 10.1038/s41467-019-10968-6
|View full text |Cite
|
Sign up to set email alerts
|

CAF hierarchy driven by pancreatic cancer cell p53-status creates a pro-metastatic and chemoresistant environment via perlecan

Abstract: Heterogeneous subtypes of cancer-associated fibroblasts (CAFs) coexist within pancreatic cancer tissues and can both promote and restrain disease progression. Here, we interrogate how cancer cells harboring distinct alterations in p53 manipulate CAFs. We reveal the existence of a p53-driven hierarchy, where cancer cells with a gain-of-function (GOF) mutant p53 educate a dominant population of CAFs that establish a pro-metastatic environment for GOF and null p53 cancer cells alike. We also demonstrate that CAFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
192
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(205 citation statements)
references
References 81 publications
(130 reference statements)
12
192
0
1
Order By: Relevance
“…In line with this study, the existence of a p53-driven hierarchy in PDAC was recently reported, where GoF p53mut cancer cells educate CAFs partially via tumour necrosis factor-alpha (TNF-a) and nuclear factor-kB (NFkB) signalling to create a permissive environment with pro-invasive cues via deposition of perlecan, an ECM proteoglycan [47]. Strikingly, these p53mut-educated CAFs caused invasion of normally poorly invasive p53null tumour cells (to the same extent as the highly invasive p53mut cancer cells) through both direct and long-range paracrine signalling [47]. Furthermore, p53null-educated CAFs, which create an environment less permissive to invasion and metastasis than p53mut-educated CAFs, can be subsequently re-educated by either p53mut cancer cells or their matched CAFs to, in turn, behave like p53mut-educated CAFs [47].…”
Section: Heterogeneity Of Caf Biomarkerssupporting
confidence: 80%
See 1 more Smart Citation
“…In line with this study, the existence of a p53-driven hierarchy in PDAC was recently reported, where GoF p53mut cancer cells educate CAFs partially via tumour necrosis factor-alpha (TNF-a) and nuclear factor-kB (NFkB) signalling to create a permissive environment with pro-invasive cues via deposition of perlecan, an ECM proteoglycan [47]. Strikingly, these p53mut-educated CAFs caused invasion of normally poorly invasive p53null tumour cells (to the same extent as the highly invasive p53mut cancer cells) through both direct and long-range paracrine signalling [47]. Furthermore, p53null-educated CAFs, which create an environment less permissive to invasion and metastasis than p53mut-educated CAFs, can be subsequently re-educated by either p53mut cancer cells or their matched CAFs to, in turn, behave like p53mut-educated CAFs [47].…”
Section: Heterogeneity Of Caf Biomarkerssupporting
confidence: 80%
“…Instead, there are several conventional and emerging biomarkers that can be used in concert to identify this diverse stromal population. The most commonly used PDAC CAF biomarkers are alpha-smooth muscle actin (a-SMA), fibroblast activation protein (FAP), vimentin, fibroblast-specific protein 1 (FSP1), podoplanin (PDPN/gp38), and platelet-derived growth factor receptor alpha and/or beta (PDGFRa/b) [23,47]; however, this list is neither all-inclusive nor entirely CAF specific [46]. In the pancreas specifically, PSC-derived CAFs lose lipid droplet expression once activated [30].…”
Section: Heterogeneity Of Caf Biomarkersmentioning
confidence: 99%
“…Work in PDAC has shown how KRAS mutation or different p53 mutational status can influence CAFs 111,136 . Mutant p53 drives TNF production by cancer cells, leading to enhanced matrix remodelling and perlecan expression by CAFs 136 . However, such studies do not preclude additional nongenetic factors influencing CAF subtype.…”
Section: Caf Heterogeneity and Plasticitymentioning
confidence: 99%
“…The functional relevance of squamous trans-differentiation in pancreatic cancer was unclear until recently, when studies from several laboratories, including our own, demonstrated that the transcription factor TP63 (delta N isoform, hereafter referred to as TP63 for simplicity) is the master regulator of the adenosquamous phenotype in PDA (Andricovich et al, 2018;Hamdan and termed iCAFs, have low expression of myCAF markers and instead produce high levels of inflammatory cytokines, such as IL-6, CXCL1, and LIF (Öhlund et al, 2017). Although the iCAF/myCAF ratio, the extent of neutrophil infiltration, and the overall level of stromal inflammation can vary significantly between PDA patients, the underlying features of cancer cells that drive these differences are only beginning to be understood (Vennin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%